Edukasi Pemasaran Varian Makanan Berbahan Dasar Ubi Di Desa Sayang, Kecamatan Jatinangor - Amalia, Rosaria Mita; Saleha, Amaliatun; Ardiati, Riza Lupi (Universitas Nusantara PGRI Kediri, 2021)
Sayang Village in Jatinangor Subdistrict is one of the villages whose agricultural products produce tuber variants, one of which is sweet potato. The processing agricultural products into culinary products is one of the factors that can help improve the community's economy. In addition to processing ingredients into food variants that have been known, modification of these types of preparations is quite important to maintain the selling power of these products. This PPM activity aims to introduce modifications to the variation of processed sweet potatoes that have been carried out by the people in Japan as well as to introduce ways of food marketing. This activity is conducted through the method of observation in the field with the technique of tapping records and the method of plunging directly into the field through direct practice (education and socialization) of making food. The theory used to study this problem comes from Setiawan Sabana (2001). Conditions in the field show that the community, especially women, consisting of mothers and young children, shows a high interest in the creation of new foods and education on the marketing of these products.